Testing Interactions in Multinomial Processing Tree Models - Kuhlmann, Beatrice G.; Erdfelder, Edgar; Moshagen, Morten (Frontiers in Psychology, 2019)
Multinomial processing tree (MPT) models allow testing hypotheses on latent psychological processes that underlie human behavior. However, its past applications have mainly been restricted to the analysis of main effects. In this paper, we adopt the interaction concept as defined in log-linear models and show why it is appropriate for MPT models. We then explain how to implement and test ordinal and disordinal two-way interaction hypotheses in MPT models. We also show how our method generalizes to higher-order interactions involving two or more factors. An empirical example from source memory and aging demonstrates the applicability of this method and allows for directly testing the associative deficit theory that age differences are larger in associative (e.g., source) memory as opposed to item memory. Throughout the paper, we explain how most analytic steps can be easily implemented in the freely available software multiTree.